ABC Medium, a New Chromogenic Agar for Selective Isolation of Salmonella spp. - Perry, John D. (American Society for Microbiology, 1999)
We describe a new chromogenic agar medium, ABC medium (αβ-chromogenic medium), which includes two substrates, 3,4-cyclohexenoesculetin-β-d-galactoside and 5-bromo-4-chloro-3-indolyl-α-d-galactopyranoside, to facilitate the selective isolation of Salmonella spp. This medium exploits the fact that Salmonella spp. may be distinguished from other members of the family Enterobacteriaceae by the presence of α-galactosidase activity in the absence of β-galactosidase activity. A total of 1,022 strains of Salmonella spp. and 300 other gram-negative strains were inoculated onto this medium. Of these, 1,019 (99.7%) strains of Salmonella spp. produced a characteristic green colony, whereas only 1 strain (0.33%) of non-Salmonella produced a green colony. A total of 283 stool samples were cultured onto desoxycholate citrate (DC) agar and ABC medium by direct inoculation and after selective enrichment in selenite broth. Overall, the sensitivity and specificity were superior for ABC medium (100 and 90.5%, respectively) than for DC agar (88 and 26.9%, respectively). We conclude that ABC medium offers a high degree of specificity for the detection of Salmonella spp. in stool samples.